Integrating QTL mapping and transcriptome analysis to provide molecular insights into gynophore-pod strength in cultivated peanut (Arachis hypogaea L.) - Chu, Wen; Zhu, Xiaofeng; Jiang, Tao; Wang, Song; Ni, Wanli (Frontiers in Plant Science, 2024)
Gynophore-pod strength is one of important mechanical properties that affect mechanized harvesting quality in peanut. Yet its molecular regulation remains elusive. In this study, gynophore-pod strength was measured across three environments by using a recombinant inbred line (RIL) population derived from a cross between Yuanza9102 and Xuzhou68-4. Both genotypic factor and environments affected gynophore-pod strength significantly, and its broad sense heritability (h2) was estimated as 0.77. Two QTLs that were stable in at least two environments were detected. qGPS.A05-1 was mapped 4cM (about 1.09Mb) on chromosome A05, and qGPS.B02-1 was mapped 3cM (about 1.71Mb) on chromosome B02. Anatomical analysis showed higher lignin content in lines with extreme high gynophore-pod strength compared to those with extreme low gynophore-pod strength. Additionally, comparative transcriptome analysis unveiled that phenylpropanoid biosynthesis was the main pathway associated with high gynophore-pod strength. Further, we predicted VJ8B3Q and H82QG0 as the candidate genes for qGPS.A05-1 and qGPS.B02-1, respectively. The two stable QTLs and their associated markers could help modify gynophore-pod strength. Our findings may offer genetic resources for the molecular-assisted breeding of new peanut varieties with improved mechanized harvesting quality.